Peran Artificial Intelligence dalam Optimalisasi Customer Relationship Management (CRM) dan Pemasaran Digital - Wira Yudha Alam; Aris Junaidi; Zulfa Risma Irnanda (Economics and Digital Business Review, 2024)
This article discusses the role of Artificial Intelligence (AI) in optimizing Customer Relationship Management (CRM) and digital marketing. The integration of AI in CRM offers companies the ability to analyze customer data more effectively, improve service personalization, and automate customer interactions through chatbots, predictive analytics, and consumer behavior pattern recognition. AI also facilitates faster decision-making in digital marketing strategies, strengthens customer experience, and improves marketing efficiency. This study shows that the implementation of AI can increase customer loyalty and give companies a competitive advantage in an increasingly complex and dynamic marketing world.